An analytical model for stator yokeless radial flux dual rotor permanent magnet synchronous machine. Issue 5 (12th May 2022) - Yang, Minglei; Zhong, Zaimin; Wang, Qinglong; Shao, Zhongshu
Abstract : Purpose: The purpose of this study is to propose an analytical model with consideration of the permeability of soft-magnetic materials, which can predict the magnetic field distribution more accurately and facilitate the initial design and parameter optimization of the machine. Design/methodology/approach: This paper proposes an analytical model of stator yokeless radial flux dual rotor permanent magnet synchronous machine (SYRFDR-PMSM) with the consideration of magnetic saturation of soft-magnetic material. The analytical model of SYRFDR-PMSM is divided into seven regions along the radial direction according to the different excitation source and magnetic medium, and the iron permeability in each region is considered based on the Maxwell–Fourier method and Cauchy's product theorem. The magnetic vector potential of each region is obtained by the Laplace's or Poisson's equation, and the magnetic field solution is determined using the boundary conditions of adjacent regions. Findings: The inner and outer air-gap flux density, flux linkage, output torque, etc., of SYRFDR-PMSM are predicted by analytical model, resulting in good agreement with that of finite element model. Additionally, the SYRFDR-PMSM prototype is manufactured and the correctness of analytical model is further verified by experiments on no-load back electromotive force and current–torque curve. Reasonable design of the slot opening width and pole arc coefficient can improve the average output torque and reduce output torque ripple. Research limitations/implications: The analytical model proposed in this paper assumes that the permeability of soft-magnetic material is a fixed value. However, the actual iron's permeability varies nonlinearly; thus, the prediction results of the analytical model will have some deviations from the actual machine. Originality/value: The main contribution of this paper is to propose an accurate magnetic field analytical model of SYRFDR-PMSM. It takes into account the permeability of soft-magnetic material and slot opening, which can quickly and accurately predict the electromagnetic performance of SYRFDR-PMSM. It can provide assistance for the initial design and optimization of SYRFDR-PMSM.